Assessing the status of household food security and its determinants in Ethiopia: Lesson from Debre Berhan town - Moges Yirgabelew; Alam Minhaj; Sisay Misganaw; Gashaw Mulu (Social Sciences and Humanities Open)
The purpose of this study is to examine the effect of industrialization on human food security in Debre Berhan city, Ethiopia. The research design used to conduct the study was descriptive, with mixed data-gathering approaches and analytical methods. Both primary and secondary data sources were used to collect the required data through laboratory tests, questionnaires, interviews, and FGDs. 227 farming households and 328 factory employees were selected systematically from and around sample industries for the sample survey. The data were analyzed using descriptive statistics, such as percentages, means, and standard deviations. In addition, the study used inferential statistical techniques, including a logistic regression model to identify relationships and patterns within the data. Whereas thematic analysis was used to assess the qualitative data. The findings of the study revealed that 52% and 53% of households and 47% and 49% of factory workers failed to achieve the minimum quantity and quality of food, respectively. Whereas, based on a proxy measure of the percentage of budgets devoted to food purchases, 83% of employees and 77% of farming households were classified as food insecure. The findings of the binary logistic regression analysis also indicated that food insecurity had a significant relationship with family size (β = 0.441, p = 0.007), livestock number (β = −0.221, p = 0.001), farmland size (β = −1.292, p = 0.061), distance from factories (β = −0.691, p = 0.005), off-farm employment (β = −2.789, p = 0.014), compensation for lost asset (β = −3.037, p = 0.002) and access to training (β = −3.037, p = 0.000). The study indicates that households with larger families, fewer livestock, smaller agricultural lands, lack of off-farm income, proximity to industries, insufficient compensation, and inadequate training experience food insecurity. The study concludes that industrial expansion negatively and significantly affected the food security of the farming and employed households. The study recommends that fair compensation, create off-farm income, prioritize community well-being, and foster sustainable development amidst industrial expansion.